Nickel-cobalt phosphide-based heterostructure as well as preparation and application thereof

Through the preparation and application of nickel-cobalt phosphide-based heterostructure catalysts, the problems of low activity and poor durability of existing catalysts under industrial-grade current density are solved, and efficient, stable and low-cost urea/hydrazine-assisted hydrogen production reaction is achieved.

CN119733536APending Publication Date: 2025-04-01SHANDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411771380.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing urea/hydrazine-assisted electrolytic hydrogen production catalysts have low catalytic activity, poor durability and slow kinetics within the industrial-grade current density range.

Method used

NixP-CoxP/NF heterostructure was prepared by potential deposition and phosphating treatment using a nickel-cobalt phosphide-based heterostructure catalyst, and a urea/hydrazine-assisted electrolytic hydrogen production device was built in an alkaline medium as an anode and a cathode.

Benefits of technology

Achieving an industrial-grade current density of 1000 mA cm-2 at lower voltages, the catalyst exhibits excellent activity, durability and kinetic properties, even better than commercial RuO2 and Pt/C catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733536A_ABST
    Figure CN119733536A_ABST
Patent Text Reader

Abstract

The invention provides preparation and application of a nickel-cobalt phosphide-based heterostructure, and belongs to the technical field of hydrogen production. The preparation method of the catalyst comprises the following steps: placing foamed nickel in a cobalt deposition solution for constant potential deposition, and washing to obtain a self-supporting CoOOH / NF nanosheet precursor; and then placing the self-supporting CoOOH / NF nanosheet precursor and sodium hypophosphite in the same container, heating a tubular furnace to 200-400 DEG C at a heating rate of 1-10 DEG C / min, carrying out phosphating treatment, and cooling to room temperature to obtain the self-supporting NixP-CoxP / NF heterostructure nanosheet catalyst. The preparation method disclosed by the invention is mild in reaction condition, simple in equipment, convenient to operate and easy for large-scale production. The prepared catalyst is low in cost, has excellent activity, durability and dynamic performance under industrial-grade current density, and is suitable for urea / hydrazine-assisted water electrolysis hydrogen production reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen production, and in particular relates to a nickel-cobalt phosphide-based heterostructure and a preparation and application thereof. Background Art

[0002] The energy crisis and environmental problems caused by the excessive consumption of traditional fossil fuels have accelerated the global transition to sustainable energy. Hydrogen energy, as a green, high calorific value, zero-pollution energy carrier, is the key to the global transition to a green economy. The technology of hydrogen production by electrolysis of water coupled with electricity generated by renewable energy is considered to be an important way to prepare high-purity green hydrogen, but its hydrogen production efficiency is severely limited by the kinetically slow anode oxygen evolution reaction (OER, 1.23 V). Although researchers have spent a lot of energy on developing highly active, highly stable and inexpensive OER catalysts, a high voltage is still required to drive the reaction. Recent studies have shown that by coupling the cathode hydrogen evolution reaction (HER) with the oxidation reaction of organic small molecules (urea, aldehydes, hydrazine hydrate, etc.) with low theoretical voltage and good thermodynamics, the cell voltage of hydrogen production by electrolysis of water can be significantly reduced, which is an effective strategy for efficient and energy-saving hydrogen production. Urea and hydrazine hydrate are considered to be common pollutants in wastewater. The thermodynamic potentials of their oxidation reactions are as low as 0.37 V and -0.33 V, respectively. If they are coupled with the cathode HER to build a water electrolysis hydrogen production system, it is possible to achieve energy-saving hydrogen production and wastewater pollutant treatment at the same time. However, the kinetic limitations of urea oxidation reaction (UOR) and hydrazine oxidation reaction (HzOR) mean that urea / hydrazine-assisted water electrolysis hydrogen production technology still has challenges, and highly active electrocatalysts are needed to increase its reaction rate. Unfortunately, most efforts are currently focused on designing advanced low-cost HER catalysts, while the development of highly active UOR and HzOR non-precious metal catalysts is far behind, not to mention trifunctional catalysts with excellent HER, UOR and HzOR performance.

[0003] In recent years, some pioneering studies have shown that interface engineering is considered to be an effective strategy for achieving simultaneous regulation of the electronic structure and active sites of bifunctional catalysts. Strong interfacial interactions between heterogeneous components can establish a large number of high-speed electron transfer channels and simultaneously induce electron coupling effects to promote electron transfer, while retaining the intrinsic catalytic activity of each component. The above advantages have been verified in advanced UOR / HER or HzOR / HER bifunctional catalysts suitable for alkaline electrolytes. For example, Jiao et al. prepared Ni3N / Mo2N heterostructure nanosheet arrays by hydrothermal and nitridation methods. The catalyst has excellent HER and UOR performance in alkaline solutions containing urea, and only requires a low working voltage of 1.36 V to reach 10 mA cm when conducting urea-assisted water electrolysis for hydrogen production. -2The current density is 7 times higher than the conventional hydrogen production rate of water electrolysis. Sui's team constructed a NiSe2 / MoSe2 Mott-Schottky heterojunction bifunctional catalyst for urea-assisted water decomposition, which achieved 100 mA cm at a potential of 1.634 V. -2 Xie et al. in situ grew a hierarchical porous nanosheet array catalyst (Ni3N-Co3N PNAs / NF) with abundant Ni3N-Co3N heterogeneous interfaces, which exhibited excellent HzOR and HER activities in an alkaline medium of hydrazine hydrate. The dual-electrode hydrazine-assisted water splitting hydrogen production electrolyzer assembled with Ni3N-Co3N PNAs / NF bifunctional electrodes as cathode and anode only required low voltages of 0.668, 0.825, 0.964, and 1.09 V to drive 100, 200, 300, and 400 mA cm, respectively. -2 Wang's team prepared a two-dimensional Ru-rich metal-organic framework catalyst (NiRu-ABDC) through a sacrificial template strategy. The results show that Ru as the active site of HER and HzOR makes NiRu-ABDC have excellent hydrazine-assisted water electrolysis hydrogen production performance, and obtains 10 mA cm -2 Despite these important advances, the reported non-precious metal UOR / HER or HzOR / HER bifunctional catalysts can only be used at current densities below the industrial level (<500 mA cm -2 ) show high activity, but cannot meet the requirements of actual large-scale industrial applications. Therefore, it is urgent to design and develop low-cost UOR / HER or HzOR / HER bifunctional catalysts with high activity, high stability and high selectivity at industrial-grade current density. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation and application of a nickel-cobalt phosphide-based heterostructure, so as to solve the technical problems of low catalytic activity, poor durability and sluggish kinetics of existing urea / hydrazine-assisted water electrolysis hydrogen production catalysts in the industrial current density range.

[0005] To achieve the above object, the present invention provides the following technical solutions: Firstly, the present invention provides a method for preparing a nickel-cobalt phosphide-based heterostructure catalyst for hydrogen evolution reaction, urea oxidation reaction and hydrazine oxidation reaction, the preparation method comprising the following steps: (1) placing nickel foam in a cobalt deposition solution for constant potential deposition at a certain potential, and then rinsing it to obtain a CoOOH / NF nanosheet precursor; (2) placing the CoOOH / NF nanosheet precursor and sodium hypophosphite in the same container, heating the tube furnace to 200-400°C at a heating rate of 1-10°C / min under an inert atmosphere and keeping the temperature for a period of time for phosphating treatment, and obtaining a NixP-CoxP / NF heterostructure catalyst after cooling to room temperature.

[0006] Preferably, in step (1), the cobalt deposition solution is prepared from 10 to 100 mmol of a soluble cobalt salt.

[0007] Preferably, in step (1), the soluble cobalt salt is Co(NO3)2·6H2O; the deposition potential voltage is -1V~-3V; the deposition time is 5~40min; and the rinsing is performed by rinsing with deionized water and anhydrous ethanol respectively.

[0008] Preferably, in step (2), the mass ratio of the self-supporting CoOOH / NF nanosheet precursor to sodium hypophosphite is 1:2-6.

[0009] Preferably, in step (2), the inert atmosphere is an argon or nitrogen atmosphere, the heating rate of the tubular furnace is 2-10°C / min, and the insulation time is 30-180min; Preferably, the application is the application in the urea / hydrazine assisted water electrolysis hydrogen production reaction at an industrial current density of 500-1000 mA cm -2 .

[0010] Preferably, the industrial-grade current density is 1000 mA cm -2 .

[0011] Secondly, the present invention provides a nickel-cobalt phosphide-based heterostructure catalyst for use in urea / hydrazine-assisted water electrolysis to produce hydrogen at an industrial-grade current density. The nickel-cobalt phosphide-based heterostructure catalyst is prepared by the above-mentioned method for preparing a nickel-cobalt phosphide-based heterostructure.

[0012] Preferably, the industrial-grade current density is 500-1000 mA cm -2 .

[0013] Preferably, the industrial-grade current density is 1000 mA cm -2 .

[0014] Secondly, the present invention provides an application of a nickel-cobalt phosphide-based heterostructure in catalyzing a urea / hydrazine-assisted water electrolysis hydrogen production reaction within an industrial current density range. When the nickel-cobalt phosphide-based heterostructure is used in a urea / hydrazine-assisted water electrolysis hydrogen production reaction at an industrial current density, in an alkaline medium containing urea / hydrazine hydrate, Ni x P-Co x The P / NF heterostructure was used as anode and cathode to construct a urea / hydrazine-assisted water electrolysis hydrogen production device; The nickel-cobalt phosphide-based heterostructure is prepared by the above-mentioned method for preparing a nickel-cobalt phosphide-based heterostructure.

[0015] Preferably, for the urea-assisted water electrolysis hydrogen production reaction, when the current density is 500 mA cm -2 When the current density is 1000 mA cm -2 When , the required working potential is 1.781~1.801 V; For the hydrazine-assisted water electrolysis reaction, when the current density is 500 mA cm -2 When the current density is 1000 mA cm -2 The required working potential is 0.317~0.337 V.

[0016] Secondly, the present invention provides a method for carrying out urea / hydrazine-assisted water electrolysis hydrogen production reaction in an industrial current density range using a nickel-cobalt phosphide-based heterostructure, wherein the method comprises: using Ni x P-Co x The P / NF heterostructure was used as the anode and cathode respectively to build a urea / hydrazine-assisted water electrolysis hydrogen production device to carry out urea / hydrazine-assisted water electrolysis hydrogen production reaction.

[0017] Preferably, in the method, for the urea-assisted water electrolysis hydrogen production reaction, when the current density is 500 mA cm -2 When the current density is 1000 mA cm -2 When , the required working potential is 1.781~1.801 V; For the hydrazine-assisted water electrolysis reaction, when the current density is 500 mA cm -2 When the current density is 1000 mA cm -2 When , the required working potential is 0.317~0.337 V; The nickel-cobalt phosphide-based heterostructure is prepared by the above-mentioned method for preparing a nickel-cobalt phosphide-based heterostructure.

[0018] Secondly, the present invention provides a device for urea / hydrazine-assisted water electrolysis to produce hydrogen at an industrial current density, wherein the cathode and anode of the device are both Ni x P-Co x P / NF heterostructure.

[0019] The Ni x P-Co x The P / NF heterostructure is a nickel-cobalt phosphide-based heterostructure, and the nickel-cobalt phosphide-based heterostructure is prepared by the above-mentioned method for preparing a nickel-cobalt phosphide-based heterostructure.

[0020] The beneficial effects of the present invention are: high catalytic performance: the Ni x P-Co x The urea / hydrazine-assisted water electrolysis hydrogen production device constructed with P / NF heterostructure as anode and cathode respectively exhibited excellent urea / hydrazine-assisted water electrolysis hydrogen production performance in alkaline media containing urea or hydrazine, and 1000 mA cm-2 could be obtained at a relatively low voltage. -2 The industrial-grade current density and the charge transfer resistance are small, which is even better than the urea / hydrazine-assisted water electrolysis hydrogen production device composed of commercial RuO2 catalyst as anode and commercial Pt / C catalyst as cathode, which means that the catalyst has better catalytic activity and kinetic performance; excellent durability: the Ni x P-Co x The urea / hydrazine-assisted water electrolysis hydrogen production device constructed with P / NF heterostructure as anode and cathode respectively can operate continuously for a long time at an industrial-grade current density of 1000 mA cm², and the applied voltage will not change significantly, and the activity loss can be ignored, showing outstanding durability and reliability. This means that the catalyst has fast mass transfer ability, excellent conductivity and good stability in actual industrial applications; low cost and easy to obtain: the present invention uses nickel, cobalt and phosphorus and other abundant elements on the surface as raw materials, which are cheap and easy to obtain, significantly reducing the production cost of water electrolysis hydrogen production catalysts, which is conducive to large-scale industrial applications and has significant benefits in promoting the development and commercial application of the hydrogen energy industry chain; simple process and strong repeatability: the present invention adopts a simple and fast low-temperature phosphating coupled constant potential electrodeposition method to prepare the catalyst. By adjusting parameters such as cobalt ion concentration, deposition potential and time, and phosphating temperature, the composition and structure of the catalyst are optimized to ensure that the process is repeatable and achieve the preparation of high-quality products; superior structure: the morphology and structural characterization reveal that Ni x P-Co xP / NF has a nanosheet morphology and a clear crystal / crystal heterogeneous interface. This structure is not only conducive to increasing the specific surface area of ​​the catalyst and exposing more active sites, accelerating mass transfer in the catalytic process, but also can optimize the electron transfer in the catalytic process, thereby increasing its reaction rate; Environmental protection and energy saving: By coupling the urea oxidation reaction (UOR) or the hydrazine oxidation reaction (HzOR) with the cathode hydrogen evolution reaction (HER), efficient and energy-saving production of green hydrogen is achieved, and at the same time, an effective solution is provided for the treatment of wastewater pollutants, achieving the dual benefits of energy saving and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 For Ni x P-Co x Linear sweep voltammetry (LSV) curves of the hydrogen production device with or without urea-assisted water electrolysis constructed with P / NF heterostructure as anode and cathode in alkaline medium (where Figure 1 a is Ni x P-Co x Comparison of linear sweep voltammetry (LSV) curves of a urea-assisted water electrolysis hydrogen production reaction device constructed with P / NF heterostructure as anode and cathode respectively and a water electrolysis hydrogen production reaction device in alkaline medium; Figure 1 b is Ni x P-Co x The P / NF heterostructure consists of anode and cathode, with Ni x Comparison of LSV curves of urea-assisted water electrolysis hydrogen production reaction devices constructed with P / NF as anode and cathode, RuO2 and Pt / C as anode and cathode, and NF as anode and cathode in alkaline medium); Figure 2 For Ni x P-Co x LSV curves of the hydrogen production device with or without hydrazine-assisted water electrolysis constructed with P / NF heterostructure as anode and cathode in alkaline medium (where Figure 2 a is Ni x P-Co x Comparison of LSV curves of a hydrazine-assisted water electrolysis hydrogen production reaction device constructed with a P / NF heterostructure as anode and cathode respectively and a water electrolysis hydrogen production reaction device in alkaline medium; Figure 1 b is Ni x P-Co x The P / NF heterostructure consists of anode and cathode, with Ni x LSV curve comparison of hydrazine-assisted water electrolysis hydrogen production reaction devices constructed with P / NF as anode and cathode, Pt / C as anode and cathode, and NF as anode and cathode in alkaline medium); Figure 3 For you x P-Co x Electron microscopy image of P / NF heterostructure (where Figure 3 a. Figure 3 b and Figure 3 c respectively Ni x P-Co x Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HR-TEM) images of P / NF heterostructures); Figure 4 For you x P-Co x X-ray diffraction pattern (XRD) of P / NF heterostructure; Figure 5 For you x P-Co x X-ray photoelectron spectroscopy (XPS) of P / NF heterostructures (where Figure 5 a. Figure 5 b and Figure 5 c respectively Ni x P-Co x Ni2p in P / NF heterostructures 3 / 2 、Co2p 3 / 2 and XPS spectra of P2p); DETAILED DESCRIPTION

[0022] In order to make the purpose, advantages and technical solutions of the present invention more clear, the present invention will be further described in detail below with reference to specific embodiments and drawings.

[0023] In the present invention, Ni is synthesized x P-Co x The raw materials required for the P / NF heterostructure urea / hydrazine-assisted water electrolysis hydrogen production catalyst can be purchased through commercial channels. Example 1

[0024] This embodiment 1 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 10 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The deposition was carried out at a constant potential of -1 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0025] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.11g, then weigh the mass of sodium hypophosphite and record it as m2=0.55g, m2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 400℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure. Example 2

[0026] This embodiment 2 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 50 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The deposition was carried out at a constant potential of -1 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0027] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.1103, then weigh the mass of sodium hypophosphite and record it as m2=0.5515, 2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 400℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure. Example 3

[0028] This embodiment 3 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The samples were deposited at a constant potential of -1 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0029] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.105g, then weigh the mass of sodium hypophosphite and record it as m2=0.525g, m2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 400℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure.

[0030] Comparison of Ni obtained under different concentrations of cobalt deposition solutions in Examples 1, 2, and 3 x P-Co x P / NF heterostructure, when the concentration of cobalt deposition solution is 100mmol, its urea / hydrazine-assisted water electrolysis hydrogen production performance is better. Example 4

[0031] This embodiment 4 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The samples were deposited at a constant potential of -2 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0032] (2) Weigh the mass of the self-supporting CoOOH / NF nanosheet precursor obtained above and record it as m1=0.107g, then weigh the mass of sodium hypophosphite and record it as m2=0.535g, m2=5m1; place the two in two different positions of the same porcelain boat, and then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 400℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co xP / NF heterostructure. Example 5

[0033] This embodiment 5 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The samples were deposited at a constant potential of -3 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0034] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.113g, then weigh the mass of sodium hypophosphite and record it as m2=0.565g, m2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 400℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure.

[0035] Comparison of the self-supporting Ni obtained under different deposition potentials in Examples 3, 4, and 5 x P-Co x The P / NF heterostructured nanosheet catalyst has better performance in urea / hydrazine-assisted water electrolysis to produce hydrogen when the deposition potential is -2V. Example 6

[0036] This embodiment 6 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The deposition was carried out at a constant potential of -2 V for 5 minutes. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0037] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.109g, then weigh the mass of sodium hypophosphite and record it as m2=0.545g, m2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 400℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure. Example 7

[0038] This embodiment 7 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The deposition was carried out at a constant potential of -2 V for 40 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0039] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.1111g, then weigh the mass of sodium hypophosphite and record it as m2=0.5555g, m2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 400℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure.

[0040] Comparison of Ni obtained at different deposition times in Examples 4, 6, and 7 x P-Co x The P / NF heterostructure has better performance in urea / hydrazine-assisted water electrolysis for hydrogen production when the deposition time is 10 min. Example 8

[0041] This embodiment 8 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The deposition was carried out at a constant potential of -2 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0042] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.1125g, then weigh the mass of sodium hypophosphite and record it as m2=0.5625g, m2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 200℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure. Example 9

[0043] This embodiment 9 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The deposition was carried out at a constant potential of -2 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0044] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.1095g, then weigh the mass of sodium hypophosphite and record it as m2=0.5475g, m2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 300℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure.

[0045] Comparative Examples 4, 8, and 9 obtained at different phosphating temperatures x P-Co x P / NF heterostructure, when the phosphating temperature is 400℃, its urea / hydrazine-assisted water electrolysis hydrogen production performance is better. Example 10

[0046] This embodiment 10 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The deposition was carried out at a constant potential of -2 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0047] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.1095g, then weigh the mass of sodium hypophosphite and record it as m2=0.5475g, m2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 400℃ for 30min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure. Embodiment 11

[0048] This embodiment 11 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The deposition was carried out at a constant potential of -2 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0049] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.1095g, then weigh the mass of sodium hypophosphite and record it as m2=0.5475g, m2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 2℃ / min, and keep it at 400℃ for 180min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure.

[0050] Comparative Examples 4, 10, and 11 obtained at different phosphating times x P-Co x The P / NF heterostructure has better performance in urea / hydrazine-assisted water electrolysis for hydrogen production when the phosphating time is 60 min. Example 12

[0051] This embodiment 12 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The deposition was carried out at a constant potential of -2 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0052] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.1093g, then weigh the mass of sodium hypophosphite and record it as m2=0.2186g, m2=5m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 1℃ / min, and keep it at 400℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Co x P / NF heterostructure. Example 13

[0053] This embodiment 13 provides a self-supporting Ni x P-Co xThe preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The samples were deposited at a constant potential of -1.5 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain a self-supporting CoOOH / NF nanosheet precursor.

[0054] (2) Weigh the mass of the self-supporting CoOOH / NF nanosheet precursor obtained above and record it as m1=0.1134g, then weigh the mass of sodium hypophosphite and record it as m2=0.6804g, m2=6m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located at the upstream position of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace at a heating rate of 10℃ / min, and keep it at 400℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain a self-supporting Ni x P-Co x P / NF heterostructured nanosheet catalyst. Embodiment 14

[0055] This embodiment 14 provides a Ni x P-Co x The preparation method of a P / NF heterogeneous structure urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: (1) Take 100 mmol of Co(NO3)2·6H2O as the cobalt deposition solution and add it to the electrolytic cell with an area of ​​1×3 cm 2 The nickel foam was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The deposition was carried out at a constant potential of -2 V for 10 min. The samples after constant potential deposition were cleaned with deionized water and anhydrous ethanol, respectively, and dried with nitrogen to obtain the CoOOH / NF nanosheet precursor.

[0056] (2) Weigh the mass of the CoOOH / NF nanosheet precursor obtained above and record it as m1=0.1134g, then weigh the mass of sodium hypophosphite and record it as m2=0.6804g, m2=6m1; place the two in two different positions of the same porcelain boat, then put the porcelain boat into the center of the tube furnace, and make the sodium hypophosphite located in the upstream position of the tube furnace. In a high-purity nitrogen atmosphere, heat the tube furnace at a heating rate of 6℃ / min, and keep it at 350℃ for 60min for phosphating treatment. After cooling to room temperature, take out the sample to obtain Ni x P-Cox P / NF heterostructure.

[0057] Comparative Example This comparative example provides a Ni x The preparation method of a P / NF urea / hydrazine-assisted water electrolysis hydrogen production catalyst comprises the following steps: Weigh a piece of 1×3 cm 2 The mass of the nickel foam is recorded as m1=0.1134g, and then the mass of the sodium hypophosphite is weighed as m2=0.562g, m2=5m1; the two are placed in two different positions of the same porcelain boat, and then the porcelain boat is placed in the center of the tube furnace, and the sodium hypophosphite is located upstream of the tube furnace. In a high-purity nitrogen atmosphere, the tube furnace is heated at a heating rate of 2℃ / min, and after reaching 400℃, it is kept warm for 60min for phosphating treatment. After cooling to room temperature, the sample is taken out to obtain Ni x P / NF nanosheet catalyst.

[0058] Experimental example Take the Ni prepared in Example 4 x P-Co x The P / NF heterostructure was tested for its catalytic performance in urea-assisted water electrolysis for hydrogen production, hydrazine-assisted water electrolysis for hydrogen production, and conventional water electrolysis for hydrogen production. x P-Co x P / NF heterostructured nanosheet catalysts were used as anode and cathode (Ni x P-Co x P / NF‖Ni x P-Co x P / NF), using alkaline solution containing urea, alkaline solution containing hydrazine hydrate and alkaline solution without urea or hydrazine hydrate as electrolyte, the electrocatalytic urea-assisted water electrolysis hydrogen production reaction performance, hydrazine-assisted water electrolysis hydrogen production reaction performance and traditional water electrolysis hydrogen production reaction performance were tested by Shanghai Chenhua CHI-604EE electrochemical workstation. In addition, the self-supporting Ni x P / NF catalysts were used as anode and cathode (Ni x P / NF‖Ni x Urea-assisted water electrolysis for hydrogen production and hydrazine-assisted water electrolysis for hydrogen production were tested under the same conditions using commercial RuO2 catalyst as anode and commercial Pt / C catalyst as cathode (RuO2‖Pt / C) and nickel foam NF as anode and cathode (NF‖NF). Figure 1 As shown: Reference Figure 1 a is Ni obtained in Example 4 x P-Cox P / NF heterostructured nanosheet catalysts were used as anode and cathode (Ni x P-Co x P / NF‖Ni x P-Co x P / NF) Performance test of electrocatalytic urea-assisted water electrolysis for hydrogen production reaction / conventional water electrolysis for hydrogen production reaction in alkaline solution with / without urea: Performance test of electrocatalytic urea-assisted water electrolysis for hydrogen production reaction was carried out in 1.0 M KOH solution containing 0.5 M urea; Performance test of electrocatalytic conventional water electrolysis for hydrogen production reaction was carried out in 1.0 M KOH solution.

[0059] in: For the traditional electrocatalytic water electrolysis reaction to produce hydrogen, Ni x P-Co x P / NF‖Ni x P-Co x P / NF requires 1.861 and 1.953 V to obtain 500 and 1000 mA cm, respectively. -2 For the electrocatalytic urea-assisted water electrolysis reaction to produce hydrogen, it only needs to apply a voltage of 1.65 and 1.781 V to obtain 500 and 1000 mA cm -2 The industrial-grade current density means that the urea-assisted water electrolysis hydrogen production reaction occurs preferentially on the Ni x P-Co x P / NF heterostructure nanosheet catalyst. x P-Co x P / NF‖Ni x P-Co x P / NF at 500 and 1000 mA cm -2 The stability of the urea-assisted water electrolysis hydrogen production reaction at industrial-grade current density was shown. After 500 hours of continuous operation, the applied voltage changes were negligible, indicating that the catalyst has excellent stability within the industrial-grade current density range.

[0060] Reference Figure 1 b is Ni obtained in Example 4 x P-Co x P / NF heterostructures as anode and cathode (Ni x P-Co x P / NF‖Ni x P-Co x P / NF), Ni obtained in comparative example x P / NF catalyst as anode and cathode (Ni xP / NF‖Ni x Performance test of the electrocatalytic urea-assisted electrolysis of water to produce hydrogen in an alkaline solution containing urea using commercial RuO2 catalyst as anode and commercial Pt / C catalyst as cathode (P / NF), and nickel foam NF as anode and cathode (NF‖NF) respectively: Performance test of the electrocatalytic urea-assisted electrolysis of water to produce hydrogen in an alkaline solution containing urea was carried out in a 1.0 M KOH solution containing 0.5 M urea.

[0061] in: In a 1.0 M KOH solution containing 0.5 M urea, Ni x P-Co x P / NF‖Ni x P-Co x P / NF obtains 500 and 1000 mA cm -2 At industrial-level current densities, the required applied cell voltages are 1.65 and 1.781 V, respectively.

[0062] In a 1.0 M KOH solution containing 0.5 M urea, Ni x P / NF‖Ni x P / NF obtained 500 and 1000 mA cm -2 At industrial-level current densities, the required applied cell voltages are 1.877 and 2.076 V, respectively.

[0063] In 1.0 M KOH solution containing 0.5 M urea, RuO2‖Pt / C obtained 500 and 1000 mA cm -2 At industrial-level current densities, the required applied cell voltages are 1.868 and 1.988 V, respectively.

[0064] In 1.0 M KOH solution containing 0.5 M urea, NF‖NF obtained 500 and 1000 mA cm -2 At industrial-level current densities, the required applied cell voltages are 2.379 and 2.497 V, respectively.

[0065] Reference Figure 2 a is Ni obtained in Example 4 x P-Co x The P / NF heterostructures were used as anode and cathode (Ni x P-Co x P / NF‖Ni x P-Co xP / NF) Performance test of electrocatalytic hydrazine-assisted water electrolysis for hydrogen production reaction / conventional water electrolysis for hydrogen production reaction in alkaline solution with / without hydrazine hydrate: Performance test of electrocatalytic hydrazine-assisted water electrolysis for hydrogen production reaction was carried out in 1.0 M KOH solution containing 0.4 M hydrazine hydrate; Performance test of electrocatalytic conventional water electrolysis for hydrogen production reaction was carried out in 1.0 M KOH solution.

[0066] in: For the traditional electrocatalytic water electrolysis reaction to produce hydrogen, Ni x P-Co x P / NF‖Ni x P-Co x P / NF requires 1.86 and 95 V to obtain 500 and 1000 mA cm, respectively. -2 For the electrocatalytic hydrazine-assisted water electrolysis reaction, it only needs to apply a voltage of 0.125 and 0.317 V to obtain 500 and 1000 mA cm -2 The industrial-grade current density means that the hydrazine-assisted water electrolysis hydrogen production reaction occurs preferentially on Ni compared with the conventional water electrolysis hydrogen production reaction. x P-Co x P / NF heterostructure. At the same time, Ni x P-Co x P / NF‖Ni x P-Co x P / NF at 500 and 1000 mA cm -2 The stability of the hydrazine-assisted water electrolysis reaction to produce hydrogen at an industrial-grade current density was studied. After 500 hours of continuous operation, the changes in the applied voltage were negligible, indicating that the catalyst showed excellent stability within the industrial-grade current density range and has potential for industrial application.

[0067] Reference Figure 2 b is Ni obtained in Example 4 x P-Co x P / NF heterostructures as anode and cathode (Ni x P-Co x P / NF‖Ni x P-Co x P / NF), Ni obtained in comparative example x P / NF catalyst as anode and cathode (Ni x P / NF‖Ni xThe performance test of the electrocatalytic hydrazine-assisted electrolysis of water to produce hydrogen was carried out in an alkaline solution containing hydrazine hydrate using commercial Pt / C catalyst as anode and cathode (Pt / C‖Pt / C) and nickel foam NF as anode and cathode (NF‖NF). The performance test of the electrocatalytic hydrazine-assisted electrolysis of water to produce hydrogen was carried out in a 1.0 M KOH solution containing 0.4 M urea.

[0068] in: In a 1.0 M KOH solution containing 0.4 M hydrazine hydrate, Ni x P-Co x P / NF‖Ni x P-Co x P / NF obtained 500 and 1000 mA cm -2 At industrial-level current densities, the required applied cell voltages are 0.125 and 0.317 V, respectively.

[0069] In a 1.0 M KOH solution containing 0.4 M hydrazine hydrate, Ni x P / NF‖Ni x P / NF obtained 500 and 1000 mA cm -2 At industrial-level current densities, the required applied cell voltages are 0.616 and 0.824 V, respectively.

[0070] In 1.0 M KOH solution containing 0.4 M hydrazine hydrate, Pt / C‖Pt / C obtained 500 and 1000 mA cm -2 At industrial-level current densities, the required applied cell voltages are 0.291 and 0.473 V, respectively.

[0071] In a 1.0 M KOH solution containing 0.4 M hydrazine hydrate, NF‖NF obtained a peak of 500 mA cm -2 At industrial-grade current densities, the required applied cell voltage is 0.716 V, and it is impossible to obtain 1000 mA cm -2 Industrial grade current density.

[0072] pass Figure 1 b and Figure 2 b Test results show that in alkaline solutions containing urea or hydrazine hydrate, the assembled Ni x P-Co x P / NF‖Ni x P-Co x The battery voltage of P / NF hydrogen production device is lower than that of Ni x P / NF‖Ni xP / NF, RuO2‖Pt / C, Pt / C‖Pt / C and NF‖NF, indicating that the prepared Ni x P-Co x The P / NF heterostructure has the highest activity and is most suitable as a catalyst for urea / hydrazine-assisted water electrolysis to produce hydrogen.

[0073] In addition, the Ni obtained in Example 4 x P-Co x The surface morphology and microstructure of P / NF catalyst were analyzed. Figure 3 A SEM image shows Ni x P-Co x The surface of the P / NF catalyst presents an ultra-thin nanosheet morphology. This unique nanosheet morphology is conducive to the exposure of active sites and can provide more mass transfer channels to accelerate the diffusion of reaction intermediates and generated gases during the catalytic process, thereby endowing Ni x P-Co x P / NF catalyst has excellent catalytic activity. Figure 3 b TEM image further reveals that Ni x P-Co x Nanosheet structure of P / NF catalyst. Figure 3 c is Ni of Example 4 x P-Co x HR-TEM image of P / NF catalyst shows that Ni x P and Co x P has a tightly bound heterointerface, which may be beneficial for promoting electron transfer. Figure 4 Ni obtained in Example 4 x P-Co x P / NF heterogeneous structure catalyst, Ni obtained in comparative example x XRD spectrum of P / NF catalyst. After analysis, it was found that Ni x P-Co x The P / NF catalyst is composed of two crystalline phases, Ni5P4 and Co2P. x The P / NF catalyst is composed of a single crystalline phase of Ni5P4. x P-Co x P / NF heterogeneous structure catalyst, Ni obtained in comparative example x The chemical structure and electronic state of the P / NF catalyst were analyzed. Figure 5 As shown in a, Ni x P-Co x Ni 2p of P / NF catalyst 3 / 2The high-resolution XPS spectrum can be fitted into three signal peaks, among which the signal peak at 852.5 eV corresponds to the Ni-P bond, while the other signal peaks at 856.8 eV and 861.6 eV are attributed to the Ni-O bond and its corresponding satellite peaks. Figure 5 b shows Ni x P-Co x Co 2p of P / NF catalysts 3 / 2 High-resolution XPS spectrum, in which the diffraction peak at the binding energy near 778.4 eV corresponds to the Co-P bond, while the two diffraction peaks at 782.1 and 786.2 eV correspond to the Co-O bond and its corresponding diffraction peaks. Figure 5 c shows Ni x P-Co x High-resolution XPS spectrum of P 2p of P / NF catalyst, in which the two diffraction peaks at 129.1 and 129.8 eV correspond to P 2p 3 / 2 and P 2p 1 / 2 , further confirming the formation of metal phosphide. Another broad signal peak near 134.4 eV is related to PO x This indicates that the phosphide surface undergoes inevitable oxidation when exposed to air. x Compared with P / NF catalyst, Ni x P-Co x The signal peaks of Ni 2p and P 2p of P / NF catalyst shifted to higher binding energy, which indicated that Ni x P and Co x There is a strong electronic interaction between Ni and P, which is beneficial to accelerate the electron transfer in the catalytic process. x P-Co x Successful preparation of P / NF heterostructured nanosheet catalysts.

[0074] Of course, the preferred embodiments described above only express several implementation methods of the present invention, and are not intended to limit the scope of the present invention. Any modifications, substitutions and improvements made without departing from the essential scope of the present invention are also included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a nickel-cobalt phosphide-based heterostructure, characterized in that: The nickel-cobalt phosphide-based heterostructure is Ni x P-Co x P / NF, the preparation method comprises the following steps: (1) placing nickel foam in a cobalt deposition solution and performing constant potential deposition at a certain deposition potential, and then rinsing the foamed nickel to obtain a CoOOH / NF nanosheet precursor; (2) placing the CoOOH / NF nanosheet precursor and sodium hypophosphite in the same container, heating the tube furnace to 200-400°C at a heating rate of 1-10°C / min in an inert atmosphere and keeping the temperature for a period of time to perform phosphating treatment, and after cooling to room temperature, obtaining Ni x P-Co x P / NF heterostructure.

2. The method for preparing a nickel-cobalt phosphide-based heterostructure according to claim 1, characterized in that: In the step (1), the cobalt deposition solution is prepared from 10 to 100 mmol of a soluble cobalt salt.

3. The method for preparing a nickel-cobalt phosphide-based heterostructure according to claim 2, characterized in that: In the step (1), the soluble cobalt salt is Co(NO3)2·6H2O; the deposition potential is -1 to -3 V; the deposition time is 5 to 40 min; and the rinsing is performed by rinsing with deionized water and anhydrous ethanol respectively.

4. The method for preparing a nickel-cobalt phosphide-based heterostructure according to claim 3, characterized in that: In the step (2), the mass ratio of the self-supporting CoOOH / NF nanosheet precursor to the sodium hypophosphite is 1:2-6.

5. The method for preparing a nickel-cobalt phosphide-based heterostructure according to claim 4, characterized in that: In the step (2), the inert atmosphere is an argon or nitrogen atmosphere, and the insulation period is 30 to 180 minutes.

6. The use of a nickel-cobalt phosphide-based heterostructure according to claim 5, characterized in that: The application is the application in the urea / hydrazine assisted water electrolysis hydrogen production reaction at an industrial current density, and the industrial current density is 500-1000 mA cm -2 .

7. A nickel-cobalt phosphide-based heterostructure for use in urea / hydrazine-assisted water electrolysis to produce hydrogen at industrial-grade current density, characterized in that: The nickel-cobalt phosphide-based heterostructure is prepared by the method for preparing a nickel-cobalt phosphide-based heterostructure according to claim 1.

8. The nickel-cobalt phosphide-based heterostructure for use in urea / hydrazine-assisted water electrolysis to produce hydrogen at an industrial-grade current density according to claim 7, characterized in that: The nickel-cobalt phosphide-based heterostructure is Ni x P-Co x P / NF, the industrial current density is 500-1000 mA cm -2 .

9. An application of a nickel-cobalt phosphide-based heterostructure in urea / hydrazine-assisted water electrolysis to produce hydrogen at industrial current density, characterized in that: The nickel-cobalt phosphide-based heterostructure is Ni x P-Co x P / NF; When the nickel-cobalt phosphide-based heterostructure is used for urea / hydrazine-assisted water electrolysis to produce hydrogen at an industrial current density, in an alkaline medium containing urea / hydrazine hydrate, Ni x P-Co x P / NF were used as anode and cathode to build a urea / hydrazine-assisted water electrolysis hydrogen production device; The nickel-cobalt phosphide-based heterostructure is prepared by the preparation method described in claim 1.

10. The use of a nickel-cobalt phosphide-based heterostructure according to claim 9 in a urea / hydrazine-assisted water electrolysis hydrogen production reaction at an industrial current density, characterized in that: For the urea-assisted water electrolysis reaction, when the current density is 500 mA cm -2 When the current density is 1000 mA cm -2 When , the required working potential is 1.781~1.801 V; For the hydrazine-assisted water electrolysis reaction, when the current density is 500 mA cm -2 When the current density is 1000 mA cm -2 The required working potential is 0.317~0.337 V.